Genotyping and drug susceptibility profiling of Prototheca sp. strains isolated from cases of protothecosis in dogs - Angelika Proskurnicka; Mateusz Iskra; Sylwia Wronka; Zofia Bakuła; Patrizia Danesi; Marconi Rodrigues deFarias; Fábio Vinícius Ramos Portilho; Márcio Garcia Ribeiro; Uwe Rösler; Rui Kano; Richard Malik; Tomasz Jagielski (Journal of Veterinary Internal Medicine)
Abstract Background Protothecosis in dogs is a rare, yet emerging disease, distinguished by its often‐aggressive clinical course and high fatality rate. Our study was conducted to enhance treatment protocols for affected dogs by better understanding the genetic diversity and drug resistance patterns of Prototheca species. Objectives To identify species and drug susceptibility profiles of an international collection of 28 Prototheca strains isolated from cases of protothecosis in dogs. Animals None. Methods Retrospective study. Species‐level identification was made for isolates from 28 dogs in 6 countries by molecular typing with the partial cytb gene as a marker. For the determination of minimum inhibitory concentrations (MICs) and minimum algicidal concentrations (MACs), the Clinical Laboratory Standards Institute (CLSI) protocol (M27‐A3) was used. Results Prototheca bovis was the most prevalent species, accounting for 75% (21/28) of the cases, followed by P. wickerhamii (18%; 5/28) and P. ciferrii (7%; 2/28). Of the 6 drugs tested, efinaconazole (EFZ) was the most potent in vitro, with its median MIC and MAC values equal to 0.125 mg/L. The lowest activity was found for fluconazole (FLU), with MIC and MAC medians of 48 mg/L and 64 mg/L, respectively. Conclusions and Clinical Importance Our study identifies P. bovis as the species that most frequently causes protothecosis in dogs, which suggests the possibility of cross‐species infection from other animals, especially cows. Additionally, it indicates that EFZ could be used in the treatment of infection in the colon.